Parental Attention and Learning Motivation of Elementary School Students: Correlation Studies - Diyah Utami Kusumaningsih; Hardi Hardi (Faculty of Tarbiyah, UIN Raden Mas Said Surakarta, 2022)
Lack of parental attention affects student learning motivation. This study aims to determine: 1) the level of attention of students' parents, 2) the level of student learning motivation, and 3) the relationship between parents' attention and students' learning motivation. The research was conducted in MI throughout the Gatak District, Sukoharjo, from January to May 2021. The data collection technique used a questionnaire of 39 grade V students. The sampling technique used cluster sampling. The results of the study showed: 1) Parents' attention was in the medium category of 18 students or 46.16%, 2) Students' learning motivation is in the medium category of 24 students or 61.54%, 3) Based on the calculation of the hypothesis test at a significance level of 5%, the results obtained are rcount (0.626) > rtable (0.316). So it can be concluded that there is a relationship between parental attention and student learning motivation. With a coefficient of determination of 0.392, the amount of contribution made by parental attention to learning motivation is 39.2% influenced by parental attention, while 60.8% is influenced by other factors not examined. The relationship between these two variables is at a strong relationship level, between 0.61-0.80